Understanding Policy for Newcomer Canadians with Emerging Print Literacy in Ontario Schools - Katie Brubacher (Canadian Society for Studies in Education, 2019)
Canada continues to be a nation of immigration where newcomer children arrive with a wide range of schooling and literacy backgrounds. This article explores the discourses of two Ontario Ministry of Education documents pertaining to students who are new to Canada and may have emerging print literacy in any language: "Supporting English Language Learners with Limited Prior Schooling - A practical guide for Ontario educators Grades 3 - 12" (2008) and "Policies and Procedures for Ontario Elementary and Secondary Schools, Kindergarten to Grade 12" (2007). Through an analysis that incorporates multiliteracies and cultural capital, the documents were analyzed for how they framed the students, how they encouraged the incorporation of students' language repertoire, and how they discuss racism. The themes that arose from this analysis included discourses of adherence to national languages, use of students' home languages as educational supports in the classroom, omission of any discussion of race, and Canada as the saving nation.